Landasan Psikologi dalam Pendidikan Islam serta Relevansinya dalam Pembentukan Karakter Moderasi Beragama di Pondok Pesantren Roudatul Muta’abidin - Vienanusa Kirana, Asmidhea; Septiana, Azizah Maulidatus; Mas’ula, Nihayatul; Eka Wahyudi, Winarto (Universitas Yudharta Pasuruan, 2022)
In its historical development, Pesantren has proven to be an Islamic Educational Institution that is very consensual in maintaining the values of religious moderation. This fact makes the Islamic pattern in Indonesia tend to be more tolerant, inclusive and strong in facing differences of opinion. This article aims to discuss how the process of Islamic boarding school education is carried out from the perspective of Islamic education psychology. The data in this study was collected through interviews and observations, and document tracking. Thisenelitian uses the Spradley model analysis technique known as taxonomic analysis. This study found that the values of moderation taught in the Roudlotul Muta'abidin Islamic boarding school include: tasamuh, tawasuth and upholding nationalism. In addition, from a psychological perspective, the strengthening of religious moderation in pesantren is strengthened through the stages of knowledge (cognitive) and habituation (habitus). Both are oriented toward students having the personality of being moderate Muslims.